If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3y + z = -6 Solving 2x + 3y + z = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 2x + 3y + -3y + z = -6 + -3y Combine like terms: 3y + -3y = 0 2x + 0 + z = -6 + -3y 2x + z = -6 + -3y Add '-1z' to each side of the equation. 2x + z + -1z = -6 + -3y + -1z Combine like terms: z + -1z = 0 2x + 0 = -6 + -3y + -1z 2x = -6 + -3y + -1z Divide each side by '2'. x = -3 + -1.5y + -0.5z Simplifying x = -3 + -1.5y + -0.5z
| d-10=-14 | | 9+(-8)= | | x^3-585=0 | | (-2i)(-2-3i)=0 | | 2+2(-5)= | | 5x-2=6x+8 | | 6x+14y=-3 | | -2x-7y=2 | | 11g=6g-15 | | 5(x+5)=60 | | 3t+17=t | | (5)(2)x+(1)(4)x=(5)(4)+4 | | 0.22y-3.5=0.12y+1-0.8y | | 3y-8=13+6y | | x-0.7=8.02 | | 2r=20 | | x-4y=28 | | 8(3b-2)= | | 3r^2+7r=-2 | | 2x^3-5x-3=0 | | -7+3=5s+21 | | m(m+5)=84 | | r^2+3r=0 | | x(4x+20)=0 | | w(w-6)=16 | | w^2-6w=16 | | a^2=24-5a | | 3a^2(x)-2a^3-x^3=0 | | -2(5n+1)=16 | | -2(4n+6)=6 | | 3(x-6)=5 | | 2(4x^2+3x+1)=0 |